2017
DOI: 10.1177/1420326x17698193
|View full text |Cite
|
Sign up to set email alerts
|

A study on microbiological contamination on air quality in hospitals in Egypt

Abstract: This study aims to evaluate airborne environmental bacteria (environmental origin), mesophilic bacteria (human related bacteria) and fungi at governmental (GH) and private (PH) hospitals, in addition to assess sink drain biofilms and dust accumulated on air conditioning filters and floor surfaces to determine if they constitute potential sources of airborne microbial biodiversity. Samples were collected from intensive care unit (ICU), operating theatre (OT), admission department (AD) and outdoor for comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 59 publications
0
33
0
Order By: Relevance
“…These organisms have been associated with symptoms of respiratory tract allergies, asthma, and infections in patients (Table 3). Bacillus and Staphylococcus have been observed to dominate the bacterial aerosol community in the indoor air samples in Africa [136,137] and some species of bacteria Acinetobacter calcoaceticus and Corynebacterium aquaticum , known as human pathogens, have been found as airborne in Bamako, Mali [120].…”
Section: Current Understanding Of Bioaerosols Associated Particulamentioning
confidence: 99%
“…These organisms have been associated with symptoms of respiratory tract allergies, asthma, and infections in patients (Table 3). Bacillus and Staphylococcus have been observed to dominate the bacterial aerosol community in the indoor air samples in Africa [136,137] and some species of bacteria Acinetobacter calcoaceticus and Corynebacterium aquaticum , known as human pathogens, have been found as airborne in Bamako, Mali [120].…”
Section: Current Understanding Of Bioaerosols Associated Particulamentioning
confidence: 99%
“…Nearly 4-11% of total microorganisms were isolated in urban air 13 . Two organisms were identified with human related bacteria viz., Allocococcus otitis in government hospital and Bacillus licheniformis in private health care centers by using Impact samples 22 . Using conventional method like settle plate technique, 57% for S. aureus and 7% for Aspergillus niger were detected 23 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that I/O ratios were consistent with those found by other studies. The I/O ratios for airborne bacteria and fungi exceeded 1 (I/O>1) in the admission departments of government hospitals in Egypt [8]. A study of airborne bacteria and fungi conducted in Korea found that I/O > 1 in public buildings, whereas in a number of hospitals the ratios were <1.0 [21].…”
Section: Potential Contributing Factors For Airborne Bacterial and Fumentioning
confidence: 97%
“…The findings from the present study are consistent with a study conducted in Singapore, which found that the airborne bacterial levels were high in a hospital lobby (445-890 cfu/m 3 ) and pharmacy (201-827 cfu/m 3 ) [7], and a study conducted in a hospital in Taiwan found that the level of airborne fungi was 699.3 cfu/m 3 in the morning and was 626.2 cfu/m 3 in the afternoon [6]. A study conducted in Egypt found that bacterial levels were 728.3 ± 673.2 cfu/m 3 in an operating theater and 1,622.2 ± 663.1 cfu/m 3 in the admission department of a governmental hospital and 512 ± 425.3 cfu/m 3 in the intensive care unit and 1,126.5 ± 763.1 cfu/m 3 in the admission department of a private hospital [8].…”
Section: Potential Contributing Factors For Airborne Bacterial and Fumentioning
confidence: 99%
See 1 more Smart Citation